2019
DOI: 10.1101/822510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Index and biological spectrum of accessible DNA elements in the human genome

Abstract: DNase I hypersensitive sites (DHSs) are generic markers of regulatory DNA and harbor disease-and phenotypic trait-associated genetic variation. We established high-precision maps of DNase I hypersensitive sites from 733 human biosamples encompassing 439 cell and tissue types and states, and integrated these to precisely delineate and numerically index ~3.6 million DHSs encoded within the human genome, providing a common coordinate system for regulatory DNA. Here we show that the expansive scale of cell and tis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…A tightly linked SNP, rs227731 (R 2 = 0.99), had a probability of 0.221; no other SNPs had probability greater than 0.01. SNP rs227731 is not in an ATAC-seq peak in any of the muscle cell types we identified nor is it in any of ENCODE's 1.3 million candidate cisregulatory elements (55,56) or any of the approximately 3.6 million DNaseI hypersensitive sites (DHS) annotated in (57), suggesting that the index SNP rs227727 is indeed the causal SNP. A previous study found that the A allele of rs227727 was associated with higher activity in an allelic luciferase assay in both human fetal oral epithelial cells (GMSM-K) and murine osteoblastic cells (MC3T3) (58).…”
Section: Integration Of Cell-type-specific Atac-seq Peaks With Uk Biomentioning
confidence: 92%
“…A tightly linked SNP, rs227731 (R 2 = 0.99), had a probability of 0.221; no other SNPs had probability greater than 0.01. SNP rs227731 is not in an ATAC-seq peak in any of the muscle cell types we identified nor is it in any of ENCODE's 1.3 million candidate cisregulatory elements (55,56) or any of the approximately 3.6 million DNaseI hypersensitive sites (DHS) annotated in (57), suggesting that the index SNP rs227727 is indeed the causal SNP. A previous study found that the A allele of rs227727 was associated with higher activity in an allelic luciferase assay in both human fetal oral epithelial cells (GMSM-K) and murine osteoblastic cells (MC3T3) (58).…”
Section: Integration Of Cell-type-specific Atac-seq Peaks With Uk Biomentioning
confidence: 92%
“…Among primary samples, we observed the highest number of DHSs in samples of early fetal brain tissue (321,338), and the lowest (34,693) in CD4+ T cells, a highly specialized cell type. From a cumulative total of 24,524,056 DHSs in individual samples, we merged all tissues and developmental stage/time samples to create a comprehensive atlas comprising 1,802,603 distinct DHSs, each of which was identified independently in one or more samples using the Index pipeline (Methods, Supplementary File 1) 17 . Within the atlas, over 467,900 elements (26%) were unique for developing or neonatal samples and were not found in DHSs from 28 adult tissues 1,16 , revealing a large untapped regulatory compartment within developmental stages.…”
Section: Regulatory Dna Landscapes Of Mouse Developmentmentioning
confidence: 99%
“…To address this, we first identified all human variants for each phenotype within the NHGRI GWAS catalog 30 and intersected these with human neural component DHSs from the ENCODE project 17 . As anticipated and previously described 7,27,28,29 , significantly enriched phenotypes included neurological traits and neuropsychiatric disorders comprising, among others, schizophrenia, neuroticism, and attention deficit hyperactivity disorder (Figure 4C).…”
Section: Using Mouse Development To Illuminate Human Diseaseassociatementioning
confidence: 99%
See 1 more Smart Citation
“…DNase I footprints define sites of direct regulatory factor occupancy on DNA and can be 10 used to discriminate sites of direct vs. indirect occupancy within orthogonal data from chromatin 11 immunoprecipitation and sequencing (ChIP-seq) experiments. Cognate transcription factors 12 (TFs) can be reliably assigned to DNase I footprints based on matching to consensus 13 sequences, enabling TF-focused analysis of gene regulation and regulatory networks 9 , and the 14 evolution of regulatory factor binding patterns within regulatory DNA 10 . DNase I is a small 15 enzyme, roughly the size of a typical transcription factor that recognizes the minor groove of 16 DNA and hydrolyzes single-stranded cleavages that, in principle, reflect both the topology and 17 the kinetics of DNA-protein interaction.…”
Section: Introductionmentioning
confidence: 99%